NAVIGATING THE PATH TO PROSPERITY: THE POWER OF PRIVATE DIRECT INVESTMENT (American Journal of Interdisciplinary Research and Development, 2024)
This article provides a comprehensive analysis of the opportunities and challenges associated with investing in Uzbekistan. The article highlights the recent economic reforms undertaken by the Uzbek government to create a more business-friendly environment and attract private direct investment. It emphasizes the importance of regulatory reforms in instilling investor confidence and fostering a conducive investment climate. However, the article also acknowledges the challenges that investors may face in Uzbekistan, including issues related to infrastructure, availability of skilled labor, legal and regulatory uncertainties, corruption risks, and governance mechanisms. It emphasizes the importance of transparency, accountability, and innovation in overcoming these challenges and maximizing the country's economic potential.